Kepok Banana Peels as Biosorbent for Mercury Sorption from Artificial Wastewater - Putri Ade Rahma Yulis; Yelfira Sari (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
The present study used adsorbents from Kepok banana peel to remove Hg (II) from artificial wastewater. Kepok banana peels are the most abundant waste from several products bananas processed. One of the ways to reduce that waste is by using it as an adsorbent. This study utilizes the adsorbent from kepok banana peels to remove Hg (II) from artificial wastewater. This is because Hg(II) is a heavy metal that is harmful A previous study showed a high amount of Hg(II) in Kuantan River, one of the River in Riau Province. The effect of initial metal concentration, adsorbent mass, and contact time was investigated to evaluate the maximum removal percentage and adsorption capacity of Kepok banana peels. The adsorption parameters studied were initial Hg (II) concentration [6.84, 7.02,8.38, and 10.05 mg/L],  adsorbent mass [10,20,30 and 40 g], and contact time variations (3,5,7 and 9 hours) where the operating conditions were 250 ml of Hg metal solution was added to each adsorbent. FTIR spectra of adsorbent showed hydroxyl, carboxylic, and amine groups in Kepok banana peels. The adsorption process found that the metal concentration variation under 6.84 mg/L initial Hg (II) concentration conditions gave the highest removal percentage of 99.7 %  and the highest adsorption capacity of 0,0758 mg/g under the condition of 10.05 mg/L  initial Hg (II) concentration. Then at adsorbent mass variation, the highest removal percentage was 94.8 % with 40 grams adsorbent mass, and the highest adsorption capacity was 0.1587 mg/g when using 10 grams adsorbent. The contact time variations gave the highest removal percentage, 95.2 %, and the highest adsorption capacity, 0.0542 mg/g, during contact for 5 hours. This study showed that Kepok banana peels had good potential for removing Hg (II) ions and could be used as a good adsorbent for removing the Hg (II) from wastewater. .